Mengolah COD Pada Limbah Laboratorium - Yenita Sandra Sari (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2019)
Laboratory liquid waste is water produced from the rest of the testing activities in a laboratory that is categorized as dangerous. This waste has a distinctive characteristic that is different from the waste originating from industrial activities because it usually has a very high diversity of types of waste even though the amount of material disposed of is relatively small. Advance Oxidation Processes (AOPs) or advanced oxidation processes are an alternative method that is suitable to be used to treat laboratory waste. This study aims to obtain the optimum dose in decreasing the concentration of Chemical Oxygen Demand (COD) with the AOPs method using Fenton reagent (H2O2 and FeSO4). The study used variations in COD concentrations of 10,090.09 mg/L, 5,009.01 mg/L and 511.71 mg/L. The results showed that the optimum dose of Fenton reagent was 1: 300 with the efficiency of decreasing COD levels for COD concentrations of 10,090.09 mg/L by 21.43%, for COD concentrations of 5,009.01 mg/L of 46.76% and for COD concentrations of 511 , 71 mg/L of 83.10%.